Analisis Perbandingan Resiliensi Ekonomi Islam dan Ekonomi Konvensional terhadap Resesi Ekonomi Global di Era Digital - Nabila Nabila; Kamila Pasyah; Ahmad Wayudi zein (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Global economic recession is a phenomenon that often arises due to market turmoil, financial sector imbalances, and rapid technological transformation. This study aims to compare the resilience of Islamic economic systems with conventional economic systems in taring global economic shocks in the digital era. The study focuses on global uncertainty in the digital era, which has increased the vulnerability of the financial system due to recession. The research findings indicate that Islamic economics has a very high level of resilience, with the implementation of risk sharing minimizing excessive speculation. In the digital era, Sharia financial technology and the optimal implementation of Ziswaf (Zakat, Infag, Sedekah, and Waqf) have been proven to strengthen the social security network and maintain the stability of the real sector. Meanwhile, conventional economies, which use interest, tend to be more vulnerable to digital financial market risks. However, conventional economies have The advantages of monetary policy flezibility and digital risk management. This study conclades that the morality of Islamic economic values combined with digital transformation can be a more robust alternative in facing the threat of a global recession in the future.